(untitled) (Razão e Fé, 2023)
The article intends to consider Latin American Theology specifically in its relationship with decolonial thought. To this end, it intends to explore the fundamental epistemological and anthropological framework of the colonial perspective within the scope of the development of a certain thought of modernity, which originated binary counterpositions with colonialist effects, whether in Europe’s relationship with the rest of the world, or within all relationships of humans with the non-human world. For the exploration of this path, Bruno Latour’s proposals are closely followed, either in the sense of a symmetrical anthropology, or in the sense of a re-animation of the planet, overcoming the dualism between subject and object. This proposal could inspire a general thought, also theological, that recovers non-colonial ways of relating humans to the world and humans to each other.